Despite a growing population, shortages remain in the area of skilled tasks : BIBB-IAB qualifications and occupational field projections up until the year 2035 asking migration refugees into account - Maier, Tobias [Verfasser]; Zika, Gerd [Verfasser]; Wolter, Marc Ingo [Verfasser]; Kalinowski, Michael [Verfasser]; Neuber-Pohl, Caroline [Verfasser]; Helmrich, Robert [Mitarbeiter]; Hummel, Markus [Mitarbeiter]; Mönnig, Anke [Mitarbeiter]; Winnige, Stefan [Mitarbeiter]; Quack, Lara [Mitarbeiter] (Bundesinstitut für Berufsbildung, 2016)
"The fourth wave of qualifications and occupational field projections pre-pared by the Federal Institute for Vocational Education and Training (BIBB) and the Institute for Employment Research (IAB) provide a summary of the German labour market's expected development up to 2035. New challenges are being presented, particularly against the background of the massive refugee migration in 2015. The direct effects of this initial rise in the population figures include higher levels of state spending and changes in the demand for housing and educational services. However, labour supply will only grow with some delay. If current educational and employment patterns continue and working times do not increase, medium-term population growth will not be sufficient to avoid long-term shortages in the area of skilled tasks. This especially affects persons who have completed vocational education and training. On the contrary, in the area of high qualifications, the labour supply shows a stronger long-term increase than demand for skilled workers for complex tasks and highly complex tasks." (Excerpt, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.1.1 Demografie; G 1.2.3.2 Anforderungen & Bedarfe; BIBB/IAB-Erhebung; Arbeitsmarktentwicklung; Berufliche Qualifikation; Projektion; Demografischer Wandel; Fachkräftebedarf; 2016-2035